Assessment of antibacterial effect of cinnamon on growth of porphyromons gingivalis from chronic periodontitis patients with deep pockets (in vitro) - Babak Amoian; Shaghayegh Noori Bayat; Zahra Molana; Ali Akbar Moghaddam Nia; Fariba Asgharpoor (Tehran University of Medical Sciences, 2014)
Background and Aims : Antibiotics are commonly used for controlling the growth of porphyromons gingivalis (P.g) which is one of the most important etiologic factors in the periodontal diseases. Different side effects of synthetics and chemical drugs such as increasing the drug resistancy in the human pathogens have led to study on the herbal antibacterial effect. The aim of this study was to evaluate the antibacterial effect of cinnamon on the growth of porphyromons gingivalis in chronic periodontitis patients with deep pockets.   Materials and Methods: In this experimental study, samples were provided from patients having pockets. After culturing the microorganism and diagnosis of P.g by gram staining and biochemical tests, cinnamon in different concentrations (10, 50, 100, 250, 500, 750 and 1500 mg/ml ) with oil solvent were prepared and placed by disks in the cultures medium. Positive controls were amoxicillin, metronidazole, ciprofloxacin, amikacin and gentamycin . Oil was negative control. Then the plates were incubated for 24 hours in 37 0 C and then non-growth halos by disk diffusion method, MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) were determined. Data were analyzed using One-way ANOVA test.   Results: The results showed that the cinnamon at the concentration of MIC=750 mg/ml had the inhibitory effects of bacteria and at the concentration of MIC=1500 mg/ml had killing effect. However, this antibacterial effect compared with commonly used antibiotics (amoxicillin, metronidazole), was much weaker (P<0.001).   Conclusion: Cinnamon showed an antimicrobial effect on porphyromonas gingivalis in chronic periodontitis patients with deep pockets.